Roversi, Bologna e gli anni Settanta - Giovannuzzi, Stefano (L'ospite ingrato, 2024)
This essay examines Roberto Roversi’s political position in the 1970s and in particular focuses on 1977 and events in Bologna following the assassination of Francesco Lorusso. Roversi disagrees with mayor Renato Zangheri’s refusal to enter into dialogue with the youth movements. Despite his affinities with the PCI, Roversi shares the protesters’ contestation of the “Historic Compromise.” Thus, with the journal «Il cerchio di gesso», he opens a fruitful dialogue with the movement, whose leaders contributed to the publication with their ideas and distinctive language. This is a decisive turn from the intellectualism that had characterized «Rendiconti». In this context – which profoundly affected Roversi’s poetry – the collaboration with Lucio Dalla was central, inspiring Roversi to revise his own language in search of new forms of communication.